Prosedur Penanganan Kedatangan Kapal MT. Bentley I Muat Crude Palm Oil (CPO) pada PT Tarunacipta Kencana Cabang Tarahan Lampung - Dzulkarnain Dzulkarnain; Yursal Yursal; Yuna Sutria (KALAO'S MARITIME JOURNAL, 2025)
The purpose of writing this paper is to find out the Procedure for Handling the Arrival of the Mt. Bentley I Ship Loading Crude Palm Oil (CPO) at PT. Tarunacipta Kencana, Tarahan Branch, Lampung. The methods applied are library research and field research by describing the Procedure for Handling the Arrival of the Mt. Bentley I Ship Loading Crude Palm Oil (CPO) at PT. Tarunacipta Kencana, Tarahan Branch, Lampung. This paper explains the procedures for the arrival of the ship and the administration to the relevant agencies regarding the arrival of the ship and coordinating with the Shipper and owner regarding the smoothness of the ship in the arrival process and the loading process. In the process of the Arrival of the Mt. Bentley I Ship, Pt. Tarunacipta Kencana as an agent provides the best service to the Mt. Bentley I Ship such as fast and efficient PKKA management, providing updated information about the ship's berthing to the owner and charter. He also explained the obstacles encountered, including cargo not being ready by the shipper and cargo analysis results not yet being released by the customs and excise agency. He also explained what can be done to ensure the ship's loading process is unimpeded and its departure is not delayed.